Implementation of Source-Based Waste Segregation Based on Bali Governor Regulation Number 47 of 2019 in Siangan Village - Anak Agung Gede Bagus Darma Putra; Ni Made Jaya Senastri; I Wayan Rideng (PT Keberlanjutan Strategis Indonesia, 2026)
The waste management issue in the Province of Bali led to the enactment of Governor Regulation of Bali Number 47 of 2019 concerning Source-Based Waste Management, which emphasizes waste segregation at the household level. This study aims to analyze the implementation of source-based waste segregation in Siangan Village, which has established a Reduce, Reuse, Recycle Waste Processing Facility (TPS3R), and to identify the inhibiting factors in its implementation. The research applies an empirical juridical method with statutory, conceptual, and socio-legal approaches. Data were collected through document studies and interviews with the Village Head, TPS3R management, and community members. The findings indicate that institutionally Siangan Village has provided adequate structural and infrastructural support, including the TPS3R facility, a scheduled collection system, and a legal basis through Village Regulation Number 7 of 2022. However, the effectiveness of implementation remains suboptimal due to systemic obstacles such as inconsistent supervision and limited human resources, as well as social constraints reflected in the lack of collective awareness and environmental legal culture. Therefore, optimizing implementation requires strengthening institutional governance and fostering sustainable community awareness.